Wildlife management in a Mexican biosphere reserve: challenges for inclusive environmental governance - López Medellín, Xavier; Brenner, Ludger; Condori Cordero, Samuel (Economía Sociedad y Territorio, 2025)
One strategy for including inhabitants in public policies are the UMAs, which generate income by using resources sustainably. However, the scope of their goals and how they have been implemented in biosphere reserves is unclear. The decision-making processes and the procedures for environmental, economic, and institutional development are analyzed. Despite the communities’ limited participation in policy design and their dependence on government funding, they play a crucial role in management. The UMAs contribute to economic diversification and generate income, but they mainly benefit landholders.